L1CAM in the early enteric and urogenital system - Pechriggl, Elisabeth Judith; Altevogt, Peter (Journal of histochemistry & cytochemistry, 2017)
L1 cell adhesion molecule (L1CAM) is a transmembrane molecule belonging to the L1 protein family. It has shown to be a key player in axonal guidance in the course of neuronal development. Furthermore, L1CAM is also crucial for the establishment of the enteric and urogenital organs and is aberrantly expressed in cancer originating in these organs. Carcinogenesis and embryogenesis follow a lot of similar molecular pathways, but unfortunately, comprehensive data on L1CAM expression and localization in human developing organs are lacking so far. In the present study we, therefore, examined the spatiotemporal distribution of L1CAM in the early human fetal period (weeks 8-12 of gestation) by means of immunohistochemistry and in situ hybridization (ISH). In the epithelia of the gastrointestinal organs, L1CAM localization cannot be observed in the examined stages most likely due to their advanced polarization and differentiation. Despite these results, our ISH data indicate weak L1CAM expression, but only in few epithelial cells. The genital tracts, however, are distinctly L1CAM positive throughout the entire fetal period. We, therefore, conclude that in embryogenesis L1CAM is crucial for further differentiation of epithelia., L1 cell adhesion molecule (L1CAM) is a transmembrane molecule belonging to the L1 protein family. It has shown to be a key player in axonal guidance in the course of neuronal development. Furthermore, L1CAM is also crucial for the establishment of the enteric and urogenital organs and is aberrantly expressed in cancer originating in these organs. Carcinogenesis and embryogenesis follow a lot of similar molecular pathways, but unfortunately, comprehensive data on L1CAM expression and localization in human developing organs are lacking so far. In the present study we, therefore, examined the spatiotemporal distribution of L1CAM in the early human fetal period (weeks 8-12 of gestation) by means of immunohistochemistry and in situ hybridization (ISH). In the epithelia of the gastrointestinal organs, L1CAM localization cannot be observed in the examined stages most likely due to their advanced polarization and differentiation. Despite these results, our ISH data indicate weak L1CAM expression, but only in few epithelial cells. The genital tracts, however, are distinctly L1CAM positive throughout the entire fetal period. We, therefore, conclude that in embryogenesis L1CAM is crucial for further differentiation of epithelia.
Published online: November 8, 2016
Gesehen am 05.07.2018